The experiences of teaching nurses in the practice of teaching in higher education: Challenges and strategies - Nunes, Marilene Rivany; Caixeta, Elcimar dos Reis; Melo, Thays Cristiny Simão; Silva, Franciele Delfina da; Silva, Léa Poliane; Nunes, Kalil Ribeiro; Rodrigues, Maria Marta do Couto Pereira (Research, Society and Development, 2023)
This is an integrative literature review, guided by the question, What are the challenges and strategies experienced by nursing professors in teaching practice. For the search, the descriptors in health sciences were adopted: teaching, teaching, higher education, nursing, pedagogy, university professors. The databases consulted were Google Scholar, MEDLINE and SCIELO. Six articles published in the first quarter of 2022 were chosen. After the descriptive analysis, it was possible to list a synthesis of knowledge revealing the logic of the theme. It was evident as challenges that most nursing professors have specific technical-assistance training in nursing, lack of pedagogical training, postgraduate training in teaching focused on theoretical content, undergraduate training in traditional teaching. As a strategy, the need to implement pedagogical training in the nursing course, pedagogical meetings, continuing and permanent education, training focused on technical, pedagogical, ethical and political improvement, creating spaces for reflection and the use of active methodology, programs of collaborative monitoring in graduation, pedagogical innovation program. It is concluded that it is necessary to design and implement institutional programs to monitor beginning teachers, which should consider welcoming among peers, partnerships with experienced teachers, institutional knowledge, investment in formal and informal spaces for dialogue between beginners and encouragement to training for the pedagogical quality of higher education and the effectiveness of an effective pedagogical practice.